Kontribusi K.H. Muh. Nuh Khaeruddin dalam Pengembangan Pondok Pesantren Al-Furqan Ereng-Ereng Kabupaten Bantaeng Tahun 1986-2004 - Iqmal; Mastanning; Akasa (Universitas Islam Negeri Alauddin, 2025)
This is a writing of the contributions of KH. Muh. Nuh Khaeruddin in the development of the Al-Furqan Ereng-Ereng Islamic Boarding School, Bantaeng Regency, from 1986 to 2004. The main objectives of this research are to detail the biography of KH. Muh. Nuh Khaeruddin, trace the history of the founding of the Al-Furqan Ereng-Ereng Islamic Boarding School, and analyze the contributions of KH. Muh. Nuh Khaeruddin to the school's development. This research employs a qualitative descriptive analysis method, utilizing both library and field data. The primary field data source was obtained through interviews, while the library data were collected from various relevant sources. The research approach encompasses historical, educational, religious, and anthropological perspectives. The research steps include heuristics, source criticism, interpretation, and historiography. The results of this research are as follows: First, KH. Muh. Nuh Khaeruddin was born in the village of Ereng-Ereng, Bantaeng, on June 6, 1940. His notable works include the book